Titanium-oxide activity during the formation of gold-bearing quartz veins: evidence for closed system behavior - Pacak,K.; Zacharias,J.; Nemec,M. (Journal of Geosciences, 2022)
Titanium contents of both vein and magmatic quartz from five Bohemian gold deposits with known P-T history were used to calculate/discuss the titanium oxide activities ( ) of natural quartz formed in the absence of Ti-buffering phases at 250-550 °C and 0.1-4 kbar.Data suggest significant variations in during vein quartz formation, due to variation of P, T, growth rate and . Negative correlation between and quartz formation temperature was documented for intrusion-related gold deposits, implying quartz precipitation under closed-system conditions (i.e., without substantial equilibration of the ascending fluid with surrounding rocks). We propose a relationship for quantifying disequilibrium quartz formation that can be readily applied to quartz with known P-T history. The relationship was tested on natural samples exhibiting both rapid and slow crystallization. An example of extreme Ti enrichment (up to ˜30 ×) in quartz, associated with its rapid growth, is described and discussed.
Keywords: thermobarometry; gold; quartz veins; titanium; Bohemian Massif